Curvilinear running demands for a fullback in Rugby League. - Nian, H. (Journal of Australian Strength and Conditioning, 2021)
A superior ability to run and sprint in rugby league may be influential to the final result of a match. A rugby league player may be required during a game to perform sprints in a curvilinear fashion to evade opponents. This is known as curvilinear running (CR). No research on CR has yet to be conducted in rugby league. Therefore, the purpose of this case study was to investigate the CR demands of fullbacks in rugby league. 4 GPSports HPU-SPI (15Hz) files were analysed from 2 fullbacks and the raw data was exported. A total of 54 runs were identified and used in the analysis. Bin intervals of 5o were used in the study. Run angles of 5-10° (n = 17) with angles of up to 40° were run during a game. No runs were purely linear in nature with all runs performed at greater than 0°. The mean velocity during each run was 6.36m/s with a maximum velocity of 9.35m/s. The maximum acceleration was 3.30m/s/s. In summary, this investigation demonstrated the highly non-linear nature of running for a fullback in rugby league. Henceforth, curvilinear running should form part of the speed training prescription to prepare a fullback for the demands of a game.